SISTEM INFORMASI PENGAJUAN DAN PENILAIAN ATLET DAN PELATIH UNTUK DANA HIBAH KONI KOTA SEMARANG - Oktaviani Risqi, Vita; Hadiono, Kristophorus (Information Technology and Telematics, 2018)
Abstract KONI of Semarang City has a grant program. The grant program has a purpose to support the achievement of program targets and government activities in the field of sports. The grant program is carried out by taking into account the principles of justice, propriety, rationality and benefits for the community. Currently, in organizing the grant program, KONI is still experiencing problems. These obstacles occur in the process of assessing athletes and trainers based on the criteria for submitting grants that take a long time. For this reason, a decision support system is needed in order to facilitate the process of applying for grants by applying the Analytical Hierarchical Process (AHP) method. So that it can facilitate sports administrators to provide an assessment of athletes and coaches when submitting proposals to get grants from KONI. The results of this study are an information system that has the ability to provide decision support in the assessment of athletes and coaches. The system can help sports administrators to submit grant proposals.